Standing Sculpture. - Apollinaire, Guillaume; Baudelaire, Charles; Boccioni, Umberto; Borghini, Vincenzio; Brancusi, Constantin; Buonarroti, Michelangelo; Calvino, Italo; Carrà, Carlo; Cellini, Benvenuto; Cook, James; Craig, Edward Gordon; De Chirico, Giorgio; et al. (Rivoli : Castello di Rivoli Museo d'Arte Contemporanea, 1987)
Andre, Carl ; Baselitz, Georg ; Beuys, Joseph ; Chamberlain, John ; Chillida, Eduardo ; Fabro, Luciano ; Flanagan, Barry ; Fontana, Lucio ; Kirkeby, Per ; de Kooning, Willem ; LeWitt, Sol ; Lüpertz, Markus ; Masson, Andre ; Melotti, Fausto ; Penck, A.R. ; Penone, Giuseppe ; Pistoletto, Michelangelo ; Rückriem, Ulrich ; Schnabel, Julian ; Serra, Richard ; Smith, David ; Visser, Carel
biografie, bibliografie
Standing Sculpture, Castello di Rivoli Museo d'Arte Contemporanea, Rivoli, 17 dicembre 1987 - 30 aprile 1988
Italiaans & Engels
boek